The weather in 1982 and 1983 - Dean Bark, L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
The 1983 weather in Kansas upset carefully laid plans and confounded the best management techniques. Yet the averages for 1982 and 1983 appear very similar. In Manhattan, the average temperatures were 54.04 F for 1982 and 54.06 for 1983. Precipitation totals were 32.88 in. for 1982 and 35.74 in. for 1983. However, those who watched their crops dry up in the summer of 1983 after delayed planting because of wet fields, and suffered with their livestock through heat stress in July and August and cold stress during December know differently. Neither our crops nor our livestock ever experience “average” weather. They experience the extremes of weather, and growth and gain are at the mercy of the variability. We can get a better picture of the last two years’ weather by looking at the actual daily values and comparing them to the normal-or average-for that time of the year.
Keywords: Beef; Temperature